Age-Associated Heterogeneity of Ty21a-Induced T Cell Responses to HLA-E Restricted Salmonella Typhi Antigen Presentation - Rudolph, Mark E.; McArthur, Monica A.; Magder, Laurence S.; Barnes, Robin S.; Chen, Wilbur H.; Sztein, Marcelo B. (Frontiers in Immunology, 2019)
Human-restricted Salmonella enterica serovar Typhi (S. Typhi) is the causative agent of typhoid fever—a life-threatening disease of great global health significance, particularly in the developing world. Ty21a is an oral live-attenuated vaccine that protects against the development of typhoid disease in part by inducing robust T cell responses, among which multifunctional CD8+ cytotoxic T lymphocytes (CTL) play an important role. Following Ty21a vaccination, a significant component of adult CTL have shown to be targeted to S. Typhi antigen presented by the conserved major histocompatibility complex (MHC) class Ib molecule, human leukocyte antigen-E (HLA-E). S. Typhi challenge studies have shown that baseline, multifunctional HLA-E responsive T cells are associated with protection from, and delayed onset of, typhoid disease. However, despite the overwhelming burden of typhoid fever in school-aged children, and due to limited availability of pediatric samples, incomplete information is available regarding these important HLA-E-restricted responses in children, even though studies have shown that younger children may be less likely to develop protective cell mediated immune (CMI) responses than adults following vaccination. To address this gap, we have studied this phenomenon in depth by using mass cytometry to analyze pediatric and adult T cell responses to HLA-E-restricted S. Typhi antigen presentation, before and after Ty21a vaccination. Herein, we show variable responses in all age strata following vaccination among T effector memory (TEM) and T effector memory CD45RA+ (TEMRA) cells based on conventional gating analysis. However, by utilizing the dimensionality reduction tool tSNE (t-distributed Stochastic Neighbor Embedding), we are able to identify diverse, highly multifunctional gut-homing- TEM and TEMRA clusters of cells which are more abundant in adult and older pediatric participants than in younger children. These findings highlight a potential age-associated maturation of otherwise conserved HLA-E restricted T cell responses. Such insights, coupled with the marked importance of multifunctional T cell responses to combat infection, may better inform future pediatric vaccination strategies against S. Typhi and other infectious diseases.